Mingling in Paedeia Café : student teachers' experiences of participating in peer-mentoring groups of pre-service and in-service teachers - Korhonen, Hanna-Maija (2015)
This study examines the experiences of student participants of Paedeia Café Finland, a part of the European PAEDEIA project. The aim of the project was to build bridges between pre-service and in-service teacher education and to develop practices for supporting new teachers in the induction phase. Five European countries (Denmark, Finland, Portugal, Sweden and Turkey) participated in the project and in Finland, Sweden and Turkey local induction programs called Paedeia Cafés were implemented. In Finland Paedeia Café was organized as peer-group mentoring for mixed group of pre-service and in-service teachers. The aim of this study was to find out how student teachers experienced Paedeia Café peer-group mentoring. The research questions were: What are the qualitatively different ways of experiencing Paedeia Café? What are the critical aspects that differentiate the ways of experiencing from each other? The method used to examine the experiences of the participants was phenomenography. The results show that student teachers experienced Paedeia Café as useful for their professional growth, but the depth of learning varied. In further development more emphasis should be placed in promoting professional development trough integrating practical experiences with theoretical understanding.